Factors Associated with Neonatal Mortality in the Neonatology Department of the Regional Hospital Center, AGADIR, MOROCCO - Mina EL Hiyani; Sakhr Ahizoune; Asmaa Mdaghri Alaoui; Amal Thimou Izgua (Mashhad University of Medical Sciences, 2023)
Background: Neonatal mortality is a major public health problem and concern worldwide. Despite significant improvement, the neonatal mortality rate is still high. The present study aimed to determine the factors associated with neonatal mortality in the Neonatology Department of the regional hospital center, Agadir, Morocco.Methods: This is a retrospective case-control study in which the records of newborns admitted during 2019 (from January 1 to December 31), in the neonatal department of the regional hospital of AGADIR were studied. Neonatal and maternal characteristics were collected from the medical record using a pre-established exploitation form. A total of 760 mother-infant pairs were selected. The association between death and study variables was evaluated using the bivariate analysis conducted by the Chi-square test. Subsequently, multivariate analysis was performed using binary logistic regression to assess the effect of each factor.Results: Significant associations were found between the onset of neonatal death and several factors such as distance traveled to the hospital facility (AOR = 3.588, 95% CI:1.952-6.594); multiparity (AOR = 3.301,95% CI: 1.919-5.680); the number of prenatal visits (AOR = 3.608,95% CI: 2.293-5.678); low birth weight (AOR = 0.314, 95% CI: 0.184-0.535); referral act  (AOR = 0.368, 95%CI: 0.208-0.652); 5-min Apgar Score (AOR = 0.104, 95%CI: 0.42- 0.257) and gestational age (AOR = 1.788,  95%CI: 0.608- 5.257).Conclusion: Neonatal mortality is associated with several preventable factors. Further preventive measures for these risk factors are required, especially in terms of pregnancy monitoring, delivery conditions, and infant management at birth.